MUSIK KRITIS DALAM MEMBANGUN KESADARAN TERHADAP KONDISI SOSIAL POLITIK: STUDI KASUS MUSIKALISASI NYELENEH KARYA JASON RANTI BAGI GENERASI MUDA - Farah Amalia; Haryadi Haryadi (Jurnal Politik indonesia (Indonesian Journal of Politics), 2021)
Critical music has the ability to describe the socio-political reality that occur in the country. Musicians describe their concerns and ideas through lyrics found in critical music. So, musicians take advantage of the function of music as mass communication. Through critical music, the delivery of socio-political phenomena can be intertwined in a more informal and relaxed manner. Especially for the younger generation who are very close to the development of music, where Indonesia is in a demographic bonus phase. In this study, researcher attempted to explain the dynamics of critical music in Indonesia's political ecosystem and how it affects the critical awareness of the younger generation. Jason Ranti describes his anxiety through the lyrics that are eccentric but rich in meaning, relaxed but not purposeless, and critical without being patronizing. Jason Ranti's critical music can build the interest of the younger generation to be more critical of the ongoing socio-political phenomena. This study uses documentation as the main data which is supported by interviews. The result of this research is that Jason Ranti has contributed in spreading critical insights to the younger generation. By understanding the meaning of eccentric musicalization through critical hermeneutic theory, Jason Ranti describes the current social phenomenon and tries to provide alternative responses for his listeners. The younger generation becomes more caring, empathetic and interested about the socio-political phenomena that are happening. Through Jason Ranti's critical music, the younger generation can take responsive actions in responding to the socio-political phenomena that are currently happening. Critical Music, Socio-Political Conditions, Jason Ranti, Younger Generation.